2011
DOI: 10.5120/3427-4782
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of Brain MR Images based on Finite Skew Gaussian Mixture Model with Fuzzy CMeans Clustering and EM Algorithm

Abstract: Segmentation is a process of converting inhomogeneous data into homogeneous data. There are many segmentation techniques available inthe literature. Among these techniques, finite Gaussian Mixture Model using EM algorithm is one mostly used. However, Gaussian Mixture Model is suited well when the image under consideration is symmetric. But in reality, medical images are asymmetric. Hence, it is needed to develop new algorithms for segmenting non -symmetric images. Therefore, skew symmetric mixture model is uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…It is also observed that the image regions have finite range of pixel intensities (-∞, +∞) and may not be symmetric and Meso kurtic [3]. In this paper, to have an accurate modeling of the feature vector, finite truncated skew Gaussian is considered by assuming that the pixel intensities in the entire image follow a Finite Truncated Skew Gaussian distribution [4][5] [6][7] [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is also observed that the image regions have finite range of pixel intensities (-∞, +∞) and may not be symmetric and Meso kurtic [3]. In this paper, to have an accurate modeling of the feature vector, finite truncated skew Gaussian is considered by assuming that the pixel intensities in the entire image follow a Finite Truncated Skew Gaussian distribution [4][5] [6][7] [8].…”
Section: Introductionmentioning
confidence: 99%